Towards Green Cities Urban Biodiversity and Ecosystem Services in China and Germany (Cities and Nature,, 2018)
The book aims to capture, describe and convey the current significance, the values and potentials of urban biodiversity and ecosystem services to scientists and professionals in the context of sustainable urban development and ongoing urbanization processes. Current developments, different approaches and future challenges in the competition of green spaces and urban land consumption in China and Germany are elaborated, discussed and illustrated within case studies and good practice examples. The strategic goal is a long-term appreciation of the potentials and increased consideration of urban green spaces in city planning and development. This book provides tangible recommendations for urban planners, politicians and stakeholders in the fields of green infrastructure at the interface of environment and urban landscape.